Development of genome‐ and transcriptome‐derived microsatellites in related species of snapping shrimps with highly duplicated genomes. (5th September 2017) - Gaynor, Kaitlyn M.; Solomon, Joseph W.; Siller, Stefanie; Jessell, Linnet; Duffy, J. Emmett; Rubenstein, Dustin R.
Abstract: Molecular markers are powerful tools for studying patterns of relatedness and parentage within populations and for making inferences about social evolution. However, the development of molecular markers for simultaneous study of multiple species presents challenges, particularly when species exhibit genome duplication or polyploidy. We developed microsatellite markers for Synalpheus shrimp, a genus in which species exhibit not only great variation in social organization, but also interspecific variation in genome size and partial genome duplication. From the four primary clades within Synalpheus, we identified microsatellites in the genomes of four species and in the consensus transcriptome of two species. Ultimately, we designed and tested primers for 143 microsatellite markers across 25 species. Although the majority of markers were disomic, many markers were polysomic for certain species. Surprisingly, we found no relationship between genome size and the number of polysomic markers. As expected, markers developed for a given species amplified better for closely related species than for more distant relatives. Finally, the markers developed from the transcriptome were more likely to work successfully and to be disomic than those developed from the genome, suggesting that consensus transcriptomes are likely to be conserved across species. Our findings suggest that the transcriptome, particularly consensus sequences from multiple species, can be a valuable source of molecular markers for taxa with complex, duplicated genomes.